2014
DOI: 10.4274/tjo.41861
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Smoking on Anterior Segment Parameters, Retinal Nerve Fiber Layer, and Pupillary Functions

Abstract: Objectives:To evaluate the alterations in the anterior segment parameters, retinal nerve fiber layer, and pupillary functions in smokers. Materials and Methods:In this case-control study, 45 eyes of 45 smokers and 45 eyes of 45 non-smoker control subjects were evaluated. All patients underwent measurement of anterior segment parameters with optical low coherence reflectometry (OLCR), mesopic and photopic pupillary diameter with an aberrometer device, retinal nerve fiber layer thickness with optical coherence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Sobacı et al (28) reported that nicotine narrowed the pupil in acute period and dilated the pupil in the chronic period. Köktekir et al (15) found that the mesopic pupil size was smaller in smokers in their study. However, since they performed this measurement 2 hours after smoking, they attributed this nding to the acute effect of smoking.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Sobacı et al (28) reported that nicotine narrowed the pupil in acute period and dilated the pupil in the chronic period. Köktekir et al (15) found that the mesopic pupil size was smaller in smokers in their study. However, since they performed this measurement 2 hours after smoking, they attributed this nding to the acute effect of smoking.…”
Section: Discussionmentioning
confidence: 61%
“…The expected effect is in the direction of pupil dilation due to the sympathetic effect (13). While pupil dilation has been reported in some studies, pupil narrowing has been reported in other studies (13,15,23,27).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Studies conducted in Korea and Turkey also found Schirmer’s test values to be reduced in smokers. [ 10 11 ] In the latter study it was reported that the values decreased further as the number of pack-years increased. On the other hand, in a study by Altinor et al .…”
Section: Discussionmentioning
confidence: 90%
“…Smoking reduces retinal blood flow and hyperoxia autoregulation ability of retinal vessels due to the vasoconstrictive influences of nicotine and changed endothelial function. 25 , 26 …”
Section: Discussionmentioning
confidence: 99%